Seismic performance evaluation of RC columns surrounded by 3D-printed outer shells including short fibers based on quasi-static cyclic loading tests - Kinomura, Koji; Murata, Satoshi; Hata, Akihito; Yamamoto, Yujin (Journal of Structural Engineering, A, 2025)
In this study, two 3DCP (3D concrete printing)-RC composite columns with 3D-outer shells which one containing 1% and the other containing 2% short fibers were produced and compared with a conventional RC column in terms of seismic performance through quasi-static cyclic loading tests. As a result, it was confirmed that the maximum horizontal strength and the ductility on both 3DCP-RC columns were enhanced in comparison with the conventional column. On the other hand, the short fiber volume contained in outer shell had only a slight impact on seismic performance, and this seemed to be caused by butt joints due to 3D-printing path which avoided the rebars embedded in the footing. Nevertheless, the 3DCP-RC column in this study demonstrated the enough high seismic performance.